Private property and real estate developers in the city of Ouagadougou: From honey to vinegar - BAZIE, Abdoul Karim; SORY, Issa (Indonesian Journal of Geography, 2025)
In Burkina Faso, Law No. 008-2023/ALT of June 20, 2023, on private real estate development includes restrictions that prevent private real estate developers from promoting land. However, almost two-thirds of these actors were engaged in this activity alone. This document therefore proposes to analyze the effects of this new legislative framework on actors involved in private real estate development in Burkina Faso. To this end, it draws mainly on qualitative data collected as part of a thesis in progress since 2021 from real estate developers, landowners, village development advisors (VDAs), sales agents, and plot buyers. Through content analysis, the article demonstrates that the revision of the legislative framework for private real estate development in Burkina Faso has led to land insecurity surrounding plots developed by private real estate developers, as well as pressure on these actors, who are struggling to make their land investments profitable. This law also affects sales agents who were speculating on land and landowners who no longer have fields to cultivate and are left with plots that are almost unattractive to customers. The results of this research call on the State to revise the texts governing land management and to strengthen control over the activities of private real estate developers.Received: 2024-11-24 Revised: 2025-08-15 Accepted: 2025-10-07 Published: 2025-11-10